Socio-Psychological Mechanisms of Specialty Image Formation During Professional Evolution - E. E. Gusarova (Управление)
Results of based on attributive theories researches of social and psychological mechanisms and regularities related to specialty image formation during professional development have been considered in this paper. Specialty image definition is presented, attributive theoretical model of the specialty image and its mechanisms of personal, object and environmental attribution is described and justified.A technique of this research carrying out has been described in the paper too, and results of empirical research of the specialty image related to persons at professional development’s various stages (pupils of profile classes, students, specialists working on the chosen specialty) have been also stated in detail. The specialty image structure with description of attributive classes and their elements has been presented. Types of attributive mechanisms and their combinations which are inherent in each of the professional development considered stages are described in this work too. It has been shown which of these mechanisms are the most effective for formation of an adequate professional picture of the world.The author has also presented possible directions for optimization of vocational training process with participation of business and educational institutions for the best adaptation of young personnel in the professional environment.